1999
DOI: 10.1038/sj.hdy.6886110
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequence variation in Ixodes pacificus (Acari: Ixodidae)

Abstract: The western black-legged tick, Ixodes paci®cus, is a primary vector of the spirochaete, Borrelia burgdorferi, that causes Lyme disease. We used variation in a 355-bp DNA portion of the mitochondrial cytochrome oxidase III gene to assess the population structure of the tick across its range from British Columbia to southern California and east to Utah. Ixodes paci®cus showed considerable haplotype diversity despite low nucleotide diversity. Maximum parsimony and isolationby-distance analyses revealed little gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 22 publications
2
40
1
1
Order By: Relevance
“…The suggested lack of phylogeography structure observed in Europe within I. ricinus s.s. ticks contrasts with the geographic genetic differentiation recorded in North America for other tick species of the I. ricinus complex (Norris et al, 1996;Kain et al, 1999;Qiu et al, 2002). Norris et al (1996), using mitochondrial DNA markers (12S and 16S rDNA) and the single strand conformation polymorphism assay (SSCP), analysed the phylogeography of I. scapularis ticks originating from north-east America (Norris et al, 1996).…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…The suggested lack of phylogeography structure observed in Europe within I. ricinus s.s. ticks contrasts with the geographic genetic differentiation recorded in North America for other tick species of the I. ricinus complex (Norris et al, 1996;Kain et al, 1999;Qiu et al, 2002). Norris et al (1996), using mitochondrial DNA markers (12S and 16S rDNA) and the single strand conformation polymorphism assay (SSCP), analysed the phylogeography of I. scapularis ticks originating from north-east America (Norris et al, 1996).…”
Section: Discussioncontrasting
confidence: 39%
“…These results were confirmed by Qiu et al (2002), who analysed the mitochondrial 16S rDNA with SSCP and reported that I. scapularis is geographically structured across the East Coast: the northern (''American clade'') and southern (''Southern clade'') populations are genetically separated and present different evolutionary and demographic histories with an effective increase of the Northern tick population size (Qiu et al, 2002). However, allozyme analysis of the mitochondrial COIII gene of another north American tick species, I. pacificus, suggested weak differentiation and the tree generated from these data revealed little geographic structure for the coastal ticks, but a separation of the Utah samples (an inland state) (Kain et al, 1999). To summarise, in North-America I. scapularis seems to have a geographic structure more marked than I. pacificus, while the variability of the genetic markers analysed is approximately the same, 12.6% (53/420, 12S rDNA, (Norris et al, 1996)) and 10.1% (36/355, COIII, (Kain et al, 1999)), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial DNA also suggested weak differentiation at a large scale in a related species, I. pacificus (Kain et al 1999). The development of other microsatellites may be a difficult task because such loci are rare in the I. ricinus species complex (Delaye et al 1998;Fagerberg et al 2001) and because the primers developed for I. uriae did not amplify I. ricinus DNA (McCoy and Tirard 2000).…”
Section: Discussionmentioning
confidence: 99%